What can voice do? Combining narrative methods and participant-produced photography to explore contemporary cancer survivorship. Issue 1 (1st January 2023) - Plage, Stefanie
Abstract : 'Giving voice' to marginalised individuals or communities is a commonly stated aim of studies employing visual research methods, particularly studies on the experiences of ill people. This points to the significance of voice as a political concept in social justice endeavours, calling for profound engagement with the ontological and epistemological assumptions around voice in visual methodologies. Drawing on Mazzei and Jackson's work on voice in qualitative inquiry, and Azoulay's understanding of photography as an infinite series of encounters, I interrogate the concept of voice in participant-led visual methodologies. To do so, I engage with my encounters with two research participants as part of a larger study on cancer survivorship conducted in Australia. These participants had cancers that are in lay and epidemiological knowledges linked with lifestyle; something that both researcher and participants grappled with and that affected their research, photographic and narrative practice. In these encounters I trace what voice can do, outlining a conceptual approach to voice integrating more-than-human agential capacities that traverse temporal, spatial and social boundaries. I argue for shifting emphasis from 'giving voice' to 'thinking with voice, ' concurrently situating research employing participant-led visual methods within the tenets of relational research more broadly.